2001
DOI: 10.1002/ajmg.10121
|View full text |Cite
|
Sign up to set email alerts
|

MTRR and MTHFR polymorphism: Link to Down syndrome?

Abstract: Polymorphisms in genes encoding the folate metabolizing enzymes methylenetetrahydrofolate reductase (MTHFR C677T) and methionine synthase reductase (MTRR A66G) have been linked to the etiology of Down syndrome. We examined the prevalence of these variant genotypes in mothers who had given birth to a child with Down syndrome (n = 48) and in control mothers (n = 192), and investigated the biochemical factors influenced by the presence of MTRR A66G and MTHFR C677T. The frequency of the MTRR variant genotypes (AG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
4
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 11 publications
10
114
4
3
Order By: Relevance
“…The present study demonstrates the association of both C677T and A1298C SNPs with mothers of DS children and a correlation with the mother's age in an Indian population. However, various other studies did not find a similar association with DS mothers (Petersen et al 2000;O'Leary et al 2002;Chadefaux-Vekemans et al 2002;Boduroglu et al 2004;Chango et al 2005;Da Silva et al 2005). Da Silva et al (2005) have shown a higher frequency of the 677T allele and elevated homocysteine levels in mothers with DS children, but consider it a minor predisposing risk factor for DS.…”
Section: A1298cmentioning
confidence: 90%
See 1 more Smart Citation
“…The present study demonstrates the association of both C677T and A1298C SNPs with mothers of DS children and a correlation with the mother's age in an Indian population. However, various other studies did not find a similar association with DS mothers (Petersen et al 2000;O'Leary et al 2002;Chadefaux-Vekemans et al 2002;Boduroglu et al 2004;Chango et al 2005;Da Silva et al 2005). Da Silva et al (2005) have shown a higher frequency of the 677T allele and elevated homocysteine levels in mothers with DS children, but consider it a minor predisposing risk factor for DS.…”
Section: A1298cmentioning
confidence: 90%
“…They also showed that a SNP in another gene associated with methionine-homocysteine metabolism, methionine synthase reductase (MTRR, OMIM*602568; chromosome 5p15.2-.3), also has an association with case mothers (with DS children). However, subsequent studies from different populations from Europe, the USA and Turkey have produced a mixed picture, finding no association with MTHFR C677T and showing either no or weak association with MTRR and another MTHFR SNP, A1298C (Chadefaux-Vekemans et al 2002;O'Leary et al 2002;Boduroglu et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 presents a flow chart of the retrieved studies and the studies excluded, with specifying reasons. Eleven studies dealt with MTHFR C677T (James et al 1999;Hobbs et al 2000;Stuppia et al 2002;O'Leary et al 2002;Boduroglu et al 2004;Acacio et al 2005;Chango et al 2005;da Silva et al 2005;Rai et al 2006;Scala et al 2006;Coppede et al 2006), seven with MTHFR A1298C (Boduroglu et al 2004;Acacio et al 2005;Chango et al 2005;da Silva et al 2005;Rai et al 2006;Scala et al 2006;Coppede et al 2006), and five with MTRR A66G (Hobbs et al 2000;O'Leary et al 2002;Chango et al 2005;da Silva et al 2005;Scala et al 2006). The studies that investigated MTHFR A1298C or MTRR A66G also investigated MTHFR C677T.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Studies were conducted in various populations of different ''racial'' groups: seven involved whites (Coppede et al 2006;Chango et al 2005;O'Leary et al 2002;Scala et al 2006;Stuppia et al 2002;Hobbs et al 2000;James et al 1999), two mixed Brazilians (da Silva et al 2005;Acacio et al 2005), one Indian (Rai et al 2006), and one Turkish (Boduroglu et al 2004). A list of the details abstracted from the studies included in the meta-analysis is provided in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation